Current State and Energy Policy Roadmap for Sustainable Adoption of Electric Vehicles in Nepal - Jha, Ajay Kumar; Darlami, Hari Bahadur; Bhattrai, Nawaraj; Karn, Subir; Neupane, Ganesh (International Journal of Energy Economics and Policy, 2025)
The transportation sector in Nepal predominantly relies on internal combustion engine vehicles, is a major contributor to greenhouse gas emissions. Despite this, electric vehicle (EV) adoption has shown significant growth, with increasing registrations of two/three-wheelers, cars, and buses. This study provides a comprehensive analysis of the current state of EV in Nepal, identifying barriers to adoption and evaluating gaps in existing policies. The methodology encompasses a policy overview, data collection through surveys and workshops, stakeholder mapping, and focal group discussions to analyze barriers and propose actionable solutions. The total registered vehicles reached 5,526,192 by mid-March 2024, with a 10% compounded annual growth rate (CAGR) from 2020, where motorcycles dominate with an 81% share. Electric vehicle imports increased by more than 75,000 units since 2020, demonstrating a 70% CAGR, with forecasts projecting 205,562 EV by 2045 at a 14% CAGR. Charging infrastructure expanded to over 600 stations by mid-March 2025, growing at 20% annually. Government policies show inconsistencies, with recent changes including a 5% increase in excise duty for vehicles up to 50 kW capacity and reduced financing limits from 80% to 60%, while simultaneously increasing financing limits for conventional vehicles from 50% to 60% in 2025. However, inconsistent fiscal policies, such as fluctuating custom, excise duties and reduced financing limits for EV, alongside persistent technical, infrastructural, and financial barriers, hinder progress. This study recommends an effective action plan to harmonize fiscal policies, expand infrastructure, and enhance financial accessibility for EV, providing a roadmap for policymakers to foster widespread adoption and achieve long-term sustainability goals in Nepal’s transportation sector.